Benefits realisation from IT-enabled innovation: A capability challenge for NHS English acute hospital trusts?. Issue 3 (4th June 2018) - Waring, Teresa; Casey, Rebecca; Robson, Andrew
Abstract : Purpose: The purpose of this paper is to address the call for more public sector empirical studies on benefits realisation (BR), to contribute to the literature on BR as a dynamic capability (DC) within the context of IT-enabled innovation in a public sector context and to highlight the challenges facing organisations if they adopt a BR competence and capability framework. Design/methodology/approach: The empirical research conducted within this paper is an exploratory survey. Exploratory surveys are particularly useful when investigating a little known phenomenon and can help to uncover or provide preliminary evidence of association among concepts. This survey was a census of all National Health Service acute hospital trusts in England. Findings: The study indicates that most hospitals that participated in the survey have a basic approach to BR and have yet to develop a more mature approach that would provide the strong micro-foundations of a BR capability. Research limitations/implications: The BR framework that has been the basis of the survey is interesting in terms of its components but is limited with regards to the micro-foundations of a benefits realisation capability within an organisation. The research suggests that organisations in the public sector need to focus much more on staff development and recruitment in the area of BR to ensure that they have the appropriate skills sets for a rapidly changing environment. Originality/value: The paper proposes a framework for BR capabilities and IT-enabled change, and suggests that although the concept of maturity is valuable when considering the micro-foundations of BR, DCs change and respond to stimuli within the external and internal environment and must be renewed and refreshed regularly.